1998
DOI: 10.1097/00004872-199816110-00012
|View full text |Cite
|
Sign up to set email alerts
|

Captopril does not improve insulin action in essential hypertension

Abstract: Captopril therapy in uncomplicated essential hypertension has no effect on peripheral or hepatic insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…8 This is in agreement with findings by Petrie et al, 7 whereas others have shown a beneficial impact. 6 ACE inhibitors are recommended first-line treatment for many patients, 26 and the combination of ACE inhibitor and calcium channel blocker now has the support of large-scale outcome trials.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8 This is in agreement with findings by Petrie et al, 7 whereas others have shown a beneficial impact. 6 ACE inhibitors are recommended first-line treatment for many patients, 26 and the combination of ACE inhibitor and calcium channel blocker now has the support of large-scale outcome trials.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with others, 6,7 we found that ACE inhibitors are at least neutral in effect on insulin action. 8 More than 1 agent is usually required to meet strict blood pressure targets, and we have also examined the effect of combination treatment on insulin action in essential hypertension. The combination of high-dose diuretic (bendroflumethiazide 5 mg) and ACE inhibitor compared with an ACE inhibitor alone reduced insulin sensitivity suggesting that low-dose diuretic should be used in combination with ACE inhibitor.…”
mentioning
confidence: 99%
“…However, many studies have shown that ACE inhibition has no beneficial effects on insulin sensitivity and the development of diabetes (Table 1) [15][16][17][18][19][20][21][22][23][24]. Unfortunately, several investigations on this issue are based on uncontrolled study designs and surrogate markers of insulin sensitivity, and are potentially confounded by the use of additional medication.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Insulin-resistant states are often associated with hypertension, and the effects of antihypertensive drugs on insulin resistance have been highlighted. Accumulated data indicate that ACE inhibitors have either no adverse effect on glucose control or insulin sensitivity [7][8][9][10] or may even improve them. [11][12][13][14][15][16][17][18][19][20] The variability of results between studies may relate to differences in experimental design, the degree of glycemia or insulin resistance, potassium balance, and the dose or duration of ACE inhibitor treatment, among others.…”
mentioning
confidence: 99%